Penerapan Antrian dan Pemesanan Online di Aplikasi Pearl Salon And BarberShop Berbasis Mobile - Rizaldi, Alfian; Pranatawijaya, Viktor Handrianus; Putra, Putu Bagus Adidyana Anugrah (Journal of Information Technology and Computer Science, 2021)
Pearl Salon and Barbershop is a provider of services and services engaged in the body care of women and men in the city of Palangkaraya. Pearl Salon and Barbershop itself wants to increase the number of turnover and maintain customer loyalty pearl in the service and services in the field of body care by creating queue applications and ordering online. Building this application uses extreme programming (xp) method software development methodology, which has stages, Exploration phase, Planning phase, Iteration Phase, Production Phase, and Maintenance Phase. At the concept stage, namely by describing the project and analysis of the system to be made. The application and website creation phase of this study used Android Studio, Firebase, XML, Java, PHP, Javascript, CSS, and JSON. The tests performed on these applications and websites use a type of Black Box testing, where the Black Box testing focuses on the requirements or functional needs of the software created. With the construction of Pearl Salon and Barbershop application can produce a system of queues and bookers that facilitate customers salon and barbershop, and realize optimal service, so that the owner can increase the trust and income of the customer salon and barbershop itself